Approach to a child with Multisystem Inflammatory Syndrome associated with COVID19. Recommendations by the Polish Paediatric Society Expert Group. Update – February 2021 - Okarska-Napierała, Magdalena; Ludwikowska, Kamila; Jackowska, Teresa; Książyk, Janusz; Buda, Piotr; Mazur, Artur; Szenborn, Leszek; Werner, Bożena; Wysocki, Jacek; Kuchar, Ernest (Pediatria Polska - Polish Journal of Paediatrics, 2021)
Multisystem Inflammatory Syndrome in Children (MIS-C) is a new clinical entity occurring in children and young adults, which is associated with the SARS-CoV-2 infection. The first cases of MIS-C were diagnosed in Poland in May 2020. Since October 2020, a significant increase in the incidence of this new disease has been observed in Poland, reflecting the increased incidence of COVID-19 in the paediatric population. MIS-C develops as a result of dysregulation of the immune system occurring 4 weeks after the SARS-CoV-2 infection. Diagnosis is based on the following criteria: a set of clinical features (including fever and signs of multiple organ damage) and elevated inflammatory markers, with exclusion of other causes. The most common complications involve the cardiovascular system: acute myocardial damage with reduced left ventricular ejection fraction, shock, and coronary artery abnormalities and arrhythmias. Mortality in Western Europe and the United States is around 1-2%. Appropriate management, including vital function support and immunomodulatory treatment, allows for a quick recovery in the vast majority of patients. This document is an updated guideline for the diagnostic and therapeutic management of children with suspected MIS-C in Poland. The most important changes concern treatment, steroid therapy, and antiplatelet therapy in particular.